Pendampingan Pencak Silat sebagai Media Dakwah dalam Mengimplementasikan Nilai Amar Makruf Nahi Munkar di Kalangan Anak Migran di Kuala Lumpur - Iqbal Nasihin Alfarizy, Muhammad; Maghfiroh, Eva; Mufid, Satuyar; Afnan Fajarudin, Akhmad (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The phenomenon of Indonesian labor migration to Malaysia has been ongoing for a long time and has had significant social impacts, particularly for migrant children. They often experience limited access to education, identity issues, and weak moral and religious development. In this context, a more creative and contextual approach to Islamic propagation is needed. Mentoring through pencak silat is a relevant alternative because, in addition to being a martial art, pencak silat also contains values ​​of discipline, respect, and spirituality that align with Islamic teachings, particularly the values ​​of enjoining good and forbidding evil. This activity aims to determine the effectiveness of pencak silat mentoring as a means of propagation in instilling the values ​​of enjoining good and forbidding evil in Indonesian migrant children in Kuala Lumpur. Furthermore, it examines how silat activities can strengthen their character, morals, and Islamic cultural identity in a multicultural environment. The method used is a service learning approach, a learning model that combines social service with a process of educational reflection. Data were obtained through observations during training activities, interviews with participants and mentors, and documentation of activities. Through this method, the process of internalizing values ​​can be directly observed in children's behavior, attitudes, and interactions. The results show that pencak silat is effective as a means of transformative da'wah (Islamic outreach). The values ​​of amar makruf (promoting good and doing good) are evident in increased positive behavior, cooperation, and honesty, while the values ​​of nahi munkar (forbidding evil) are reflected in children's ability to control themselves and avoid negative behavior. This approach not only conveys da'wah but also fosters Islamic character that is applicable in everyday life.